2015
DOI: 10.1021/acs.est.5b02151
|View full text |Cite
|
Sign up to set email alerts
|

Ship Compliance in Emission Control Areas: Technology Costs and Policy Instruments

Abstract: This paper explores whether a Panama Canal Authority pollution tax could be an effective economic instrument to achieve Emission Control Area (ECA)-like reductions in emissions from ships transiting the Panama Canal. This tariff-based policy action, whereby vessels in compliance with International Maritime Organisation (IMO) ECA standards pay a lower transit tariff than noncompliant vessels, could be a feasible alternative to petitioning for a Panamanian ECA through the IMO. A $4.06/container fuel tax could in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 16 publications
0
15
0
2
Order By: Relevance
“…At the moment, for ships operating both in-and outside of SECAs, dual fuel machinery allowing the ships to use fuels with different sulfur contents (HFO and LFO) seems to be the optimal solution in economic terms (Yang et al, 2012;Patricksson and Erikstad, 2017), whereas LNG appears the optimum proposed solution when both the environmental and the economic points of view are considered (Ammar and Seddiek, 2017). However, MSSs seem to be cost-effective for vessels operating mainly or entirely within SECAs (Ciatteo et al, 2014;Carr and Corbett, 2015): it has been estimated that for Finnish shipping companies alone, fitting MSSs into ships would bring cost savings around 62-85 million Euros a year compared to switching to more expensive fuel types with lower sulfur content (Kalli, 2012).…”
Section: <Figure_4>mentioning
confidence: 97%
“…At the moment, for ships operating both in-and outside of SECAs, dual fuel machinery allowing the ships to use fuels with different sulfur contents (HFO and LFO) seems to be the optimal solution in economic terms (Yang et al, 2012;Patricksson and Erikstad, 2017), whereas LNG appears the optimum proposed solution when both the environmental and the economic points of view are considered (Ammar and Seddiek, 2017). However, MSSs seem to be cost-effective for vessels operating mainly or entirely within SECAs (Ciatteo et al, 2014;Carr and Corbett, 2015): it has been estimated that for Finnish shipping companies alone, fitting MSSs into ships would bring cost savings around 62-85 million Euros a year compared to switching to more expensive fuel types with lower sulfur content (Kalli, 2012).…”
Section: <Figure_4>mentioning
confidence: 97%
“…A 2015 paper evaluated technology costs and policy instruments with regard to ship compliance in ECAs (Carr and Corbett, 2015). This work showed that vessels would need to operate within an ECA for more than 4500 hours annually before retrofitting them with open-loop emissions scrubbers would become cost-effective.…”
Section: Air Pollution Technologiesmentioning
confidence: 99%
“…Investment costs for new build vessels are estimated to be EUR 4-6 million according to some sources (EMSA, 2010). Other sources however show much higher estimations: according to Carr and Corbett (2015) Nuclear marine propulsion is the propulsion of a ship or submarine with heat provided by a nuclear power plant. The power plant heats water to produce steam which in turn powers the steam turbines and turbo generators.…”
Section: Liquified Natural Gasmentioning
confidence: 99%
“…Ship time in ECAs: Fuel switching is the lowest cost retrofit option for vessels operating fewer than 4 500 hours annually in SECAs (Carr and Corbett, 2015). As measures to comply with the ECA requirements in 2015, scrubbers are less cost effective for deep-sea vessels as the portion of time they spend in ECAs is relatively low; retrofitting open-loop scrubbers currently only makes sense for vessels such as ferries or short-sea vessels that operate within ECAs for more than 50% of the year (Carr and Corbett, 2015). The calculations are very different for newbuilds and crucially depend on assumptions about fuel price developments.…”
Section: Which Compliance Options Under Which Conditions?mentioning
confidence: 99%
See 1 more Smart Citation